452 A pesticide exposure study using 24-hour biomonitoring and dermal sampling to determine total uptake and the routes of exposure. (24th April 2018) - Connolly, Alison; Jones, Kate; Galea, Karen S; Basinas, Ioannis; Kenny, Laura; McGowan, Padraic; Coggins, Marie
Abstract : Introduction: A pilot exposure assessment study using biomonitoring was conducted in Ireland to determine the likelihood of exposure to pesticides among amenity horticulturalists. A spot sampling approach was employed of workers using pesticides, had urinary pesticide concentrations in post-work samples with a geometric mean (geometric standard deviation) of 0.66 (1.11) µg L -1 for glyphosate and 0.29 (1.69) µg L -1 for fluroxypyr. The study showed a potential for pesticide exposure during horticulture amenity work, higher than average environmental exposure levels and warranted further investigation. Methods: In 2017, an exposure assessment study involving 24 hour biomonitoring will take place to evaluate pesticide exposure among these workers. Workers will be grouped into four similar exposure groups based on application method and active ingredient used, glyphosate or fluroxypyr. Three urine samples will be collected for each task, a sample before the task begins, a sample within one hour of the task completion and a following morning void. The potential routes of exposure, will be examined through the collection of additional dermal, glove and potentially contaminated object wipe samples. Dermal wipes of the hands and the perioral region will be taken before and after the task and glove analysis will be conducted. Detailed contextual information will be collected by the researcher to support all samples collected. Results: The biomonitoring results will indicate the extent of pesticide uptake for each task. Correlation between the dermal and biomonitoring samples will be investigated to explore the contribution of dermal exposure. The perioral and the contaminated object wipes alongside the contextual information will be used to determine the potential exposure from inadvertent ingestion. Discussion: This study will provide a comprehensive biomonitoring dataset describing amenity horticultural user's exposure to glyphosate and fluroxypyr and the contribution of dermal and inadvertent ingestion routes on total body burden of pesticides.